Is the interpretation of rapid antigen testing for respiratory syncytial virus as simple as positive or negative?. Issue 2 (20th August 2013) - Walsh, Paul; Overmyer, Christina; Hancock, Christine; Heffner, Jacquelyn; Walker, Nicholas; Nguyen, Thienphuc; Shanholtzer, Lucas; Caldera, Enrique; Pusavat, James; Mordechai, Eli; Adelson, Martin E; Iacono, Kathryn T
Abstract : Objective: To measure the performance characteristics of an immunochromatographic rapid antigen test for respiratory syncytial virus (RSV) and determine how its interpretation should be contextualised in patients presenting to the emergency department (ED) with bronchiolitis. Design: Diagnostic accuracy study of a rapid RSV test. Setting: County hospital ED. Intervention: We took paired nasal samples from consecutively enrolled infants with bronchiolitis and tested them with a rapid immunochromatographic antigen test and reverse transcriptase PCR gold standard. Outcome measures: Sensitivity, specificity, the effect of point prevalence, clinical findings and overall context on predictive values. We used these to construct a graphical contextual model to show how the results of RSV antigen tests from infants presenting within 24 h should influence interpretation of subsequent antigen tests. Results: We analysed 607 patients. The sensitivity and specificity for immunochromatographic testing was 79.4% (95% CI 73.9% to 84.2%) and 67.1% (95% CI 61.9% to 72%) respectively. We found little evidence of spectrum bias. In our contextual model the best predictor of a positive RT-PCR test was a positive antigen test OR 5.47 (95% CI 3.65 to 8.18) and the number of other infants having positive tests within 24 h OR 1.48 (95% CI 1.26 to 1.72) per infant. Increasing numbers presenting to the ED with bronchiolitis in a given day increases the probability of RSV infection. Conclusions: The RSV antigen test we examined had modest performance characteristics. The results of the antigen test should be interpreted in the context of the results of previous tests.